การพัฒนาแนวทางการส่งเสริมการทำวิจัยในชั้นเรียนของครูในโรงเรียนประถมศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษานครพนม เขต 1 - Suriyon, Phatwali; Suwannakud , Ratchata; Prasantree, Tatsana (Journal of Graduate School Sakon Nakhon Rajabhat University, 2022)
The objectives of this research were 1) to examine the current and desirable conditions of conducting classroom of teachers under Nakhon Phanom Primary Educational Service Area Office 1, 2) to examine the necessary needs for promoting primary school teachers’ practices in conducting classroom research, and 3) to establish guidelines for promoting primary school teachers’ practices in conducting classroom research. The sample group, obtained through stratified random sampling, consisted of 320 teachers working in primary schools under Nakhon Phanom Primary Educational Service Area Office 1. The sample size was determined by comparing the tables of Krejcie and Morgan. The research tools included: 1) a set of questionnaires on the current conditions in conducting classroom research of primary school teachers with the item objective congruence index (IOC) of 1.00 for all items, the discriminative power ranging from .51 to .92, and the reliability of .93; 2) a set of questionnaires on the desirable conditions on learning management using classroom research of primary school teachers with IOC of 1.00 for all items, the discriminative power ranging from .55 to .81, and the reliability of .98; 3) a structured interview form, and 4) a form for assessing the appropriateness and the feasibility of guidelines for developing primary school teachers’ practices for conducting classroom research. The statistics were percentage, mean, standard deviation, and content analysis. The results of the research revealed that 1) the current conditions in conducting classroom research of primary school teachers were overall at a high level, and the desirable conditions of conducting classroom research of primary school teachers were overall at the highest level, 2) The highest level of needs for conducting classroom research of primary school teachers was the promotion of the success of conducting classroom research, and 3) The guidelines for promoting practices of conducting classroom research of primary school teachers were overall at the highest level of appropriateness and the feasibility was overall at a high level.